Hepatoprotective and nephroprotective activity of hydroalcoholic extract of Ipomoea staphylina leaves (Bangladesh Journal of Pharmacology, 2013)
The present study was undertaken to investigate the protective effect of hydroalcoholic extract of leaves of Ipomoea staphylina against carbon tertrachloride- and gentamicin-induce hepatotoxicity and nephrotoxicity in rats respectively. The extract (200 mg/kg, p.o) showed hepatoprotective activity against carbon tetrachloride-induced hepatotoxicity  by significantly (p